143 Incidence, predictors, and clinical impact of transient left bundle branch block in patients undergoing transcatheter aortic valve implantation. (8th December 2021) - Leone, Attilio; Franzone, Anna; Avvedimento, Marisa; Piccolo, Raffaele; Angellotti, Domenico; Mariani, Andrea; Castiello, Domenico Simone; Ilardi, Federica; Manzo, Rachele; Iapicca, Cristina; Serafino, Luigi Di; Cirillo, Plinio; et al.
Abstract: Aims: This study aims to evaluate the incidence and prognostic impact of transient left bundle branch block (LBBB) in patients undergoing transcatheter aortic valve implantation (TAVI) with balloon-expandable or self-expanding valves. Clinical, echocardiographic and electrocardiographic predictors of transient LBBB were also investigated. Methods and results: 197 patients treated with TAVI at Federico II University hospital, Naples, Italy were enrolled. Electrocardiograms (ECGs) were obtained before and after TAVI procedure, at discharge and at 30-day follow-up. ECGs were anonymously digitalized and analysed by five cardiologists. Transient LBBB was defined as LBBB regressed within 30 days after procedure. All ECGs for each patient were analysed by the same cardiologist. The primary endpoint of the study was all-cause mortality and permanent pacemaker implantation (PPI) at 1-month after TAVI. Secondary endpoints included cerebrovascular accidents, acute myocardial infarction, vascular complications, acute kidney injury, endocarditis, and re-hospitalization for all causes. Out of 197 patients enrolled, 54 (27.4% ) developed transient LBBB. Among patients with transient LBBB, 70.4% were female. Mean age was higher in transient LBBB group compared with control group (81.0 ± 6.4 years, vs. 78. 6 ± 6.5 years; P = 0.022). From logistic analysis, peak transvalvular gradient (OR: 1.01, 95% CI: 0.93–1.00; P < 0.034) and left ventricular ejection fraction (LVEF) (OR: 0.96, 95% CI: 0.93–0.99, P < 0.012) were identified as predictive factors of transient LBBB. No differences between the two studied groups were observed in primary and secondary endpoints (all-cause mortality: 1.9% vs. 0.7%; P = 0.46; PPI: 9.6% vs. 12%; P = 0.80). Conclusions: Peak transvalvular gradient and LVEF predict onset of transient LBBB, a common conduction disturbance after TAVI. Onset of transient LBBB does not correlate with worse clinical outcomes at 30 days.